Physiological profiles of elite senior wrestlers - Yoon, J. (Sports Medicine, 2002)
To perform excellently in international competitions, wrestlers have to achieve an excellent level of physical fitness and physical condition during training. This article reviews the physiological profiles of elite wrestlers. In general, successful wrestlers showed higher dynamic and isokinetic strength than unsuccessful wrestlers. In particular, upper body strength and anaerobic power were significantly different between the two groups. Aerobic capacity is one of the most important physical factors to achieve good results in wrestling competitions. The maximal oxygen uptake of national and international wrestlers taking part in international competition has been shown to be about 53 to 56 ml/kg/min. Around the time of the Seoul Olympics, typical values for wrestlers were about 60 ml/kg/min, with values of >70 ml/kg/min in some cases (the latter being similar to values reported for some endurance runners). The flexibility of the wrestlers was found to be lower than that of weight lifters and gymnasts. However, the flexibility of top-level wrestlers was higher than that of lower level wrestlers. To fully understand the physiological profiles of successful wrestlers, further research regarding anaerobic and aerobic energy metabolism, cardiopulmonary responses, body fat content, and changes in muscle hypertrophy both during the wrestling season and off-season is warranted.